Whatever happened to the "Goodwin pattern"? - Mark Setterfield (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
The "Goodwin pattern" - an anti-clockwise rotation in real activity x wage share space recurring at intervals that correspond roughly to the duration of business cycles - is an enduring feature of high-frequency dynamics in capitalist economies. It is well known that the centre or focus of this rotation shifts over time. More recently, however, the Goodwin pattern seems to have broken down, the wage share no longer increasing as the real economy improves over the course of short-term booms. In this paper, the breakdown of the Goodwin pattern is associated with the consolidation of an "incomes policy based on fear" that is part-and-parcel of neoliberalism. As a result of this incomes policy based on fear, the institutional structure of the labour market disciplines labour at any rate of unemployment. This decouples wage-share dynamics from the state of the real economy, with the result that as recently witnessed, the wage share is rendered invariant to tightening of the labour market in the course of short-term cyclical booms.
Keywords: E11; E12; E25; E64; 330; Goodwin pattern; distributional conflict; worker insecurity; incomes policy based on fear